Synthesis, characterization and structures of solvent-mediated Na(I)–Pd(II) heterometallic complexes containing [Pd(barb)4]2− units (barb = 5, 5-diethylbarbiturate). Issue 15 (2nd August 2016) - Icsel, Ceyda; Yilmaz, Veysel T.; Büyükgüngör, Orhan
Abstract: Reaction of Na2 [PdCl4 ] with the sodium salt of 5, 5-diethylbarbituric acid (barbH) led to the formation of two complexes, [PdNa2 (μ-barb)4 (DMSO)2 ]·2H2 O·DMSO (1 ), and {[PdNa2 (μ-barb)4 (H2 O)]·3H2 O} n (2 ). The complexes were characterized by elemental analysis, FT-IR, NMR, and X-ray crystallography. Complex1 was crystallized from H2 O/DMSO (1 : 1, v : v) and2 was crystallized in H2 O. Both complexes contain square planar [Pd(barb)4 ] 2− moieties, in which Pd(II) is coordinated by four barb ligands via the negatively charged nitrogens. In addition to the coordination of a DMSO ligand, two Na(I) ions in1 are bridged by carbonyl O of four barb ligands in the [Pd(barb)4 ] 2− unit, while the Pd(II) and Na(I) ions in2 are bridged by the barb ligands in a tetradentate bridging fashion leading to a 2-D polymeric network. The bridging of metal centers in both complexes result in a significantly short Na−Pd distance of ca. 2.95 Å. Contrary to2, the coordination of DMSO to Na(I) in1 avoids the extension of the polymeric structure. Abstract :